Autobiographical memory unknown: Pervasive autobiographical memory loss encompassing personality trait knowledge in an individual with medial temporal lobe amnesia. (February 2022) - Wank, Aubrey A.; Robertson, Anna; Thayer, Sean C.; Verfaellie, Mieke; Rapcsak, Steven Z.; Grilli, Matthew D.
Abstract: Autobiographical memory consists of distinct memory types varying from highly abstract to episodic. Self trait knowledge, which is considered one of the more abstract types of autobiographical memory, is thought to rely on regions of the autobiographical memory neural network implicated in schema representation, including the ventromedial prefrontal cortex, and critically, not the medial temporal lobes. The current case study introduces an individual who experienced bilateral posterior cerebral artery strokes resulting in extensive medial temporal lobe damage with sparing of the ventromedial prefrontal cortex. Interestingly, in addition to severe retrograde and anterograde episodic and autobiographical fact amnesia, this individual's self trait knowledge was impaired for his current and pre-morbid personality traits. Yet, further assessment revealed that this individual had preserved conceptual knowledge for personality traits, could reliably and accurately rate another person's traits, and could access his own self-concept in a variety of ways. In addition to autobiographical memory loss, he demonstrated impairment on non-personal semantic memory tests, most notably on tests requiring retrieval of unique knowledge. This rare case of amnesia suggests a previously unreported role for the medial temporal lobes in self trait knowledge, which we propose reflects the critical role of this neural region in the storage and retrieval of personal semantics that are experience-near, meaning autobiographical facts grounded in spatiotemporal contexts.